If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 5 + 10y = 9y + -9 Reorder the terms: 5 + 10y = -9 + 9y Solving 5 + 10y = -9 + 9y Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '-9y' to each side of the equation. 5 + 10y + -9y = -9 + 9y + -9y Combine like terms: 10y + -9y = 1y 5 + 1y = -9 + 9y + -9y Combine like terms: 9y + -9y = 0 5 + 1y = -9 + 0 5 + 1y = -9 Add '-5' to each side of the equation. 5 + -5 + 1y = -9 + -5 Combine like terms: 5 + -5 = 0 0 + 1y = -9 + -5 1y = -9 + -5 Combine like terms: -9 + -5 = -14 1y = -14 Divide each side by '1'. y = -14 Simplifying y = -14
| 0=-9(y+5) | | 7x+5+4x+8= | | 6p=5p+9 | | 3(x+2.59)=2x | | n+18=16 | | -5p-8+3-p= | | 6x+26=13x-37 | | 7+5y=4y-4 | | 5v+8+9v+7= | | 9(d+-1)+d=11 | | k^2-3k-8=0 | | 9(b-1)+b=11 | | 14+10y=2y-2 | | -v-3v+15= | | 7x+8=8x-20 | | 3(-z+6)+2z=-18 | | b-3-2b= | | 3n+4n=14 | | 9m-5m= | | 2x^2+6x+28=0 | | 3a-3+a= | | x^2+8x+99=0 | | 4m-16-9= | | 3x+4=8-4 | | 5-(x+8)= | | -3+2v+1= | | .5x-11=9 | | b+3b= | | -5k-k+10= | | 5+9(x+7)=122 | | -6n+4+5-n= | | 15x+1=15X |